2002
DOI: 10.1038/nature737
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitination of p53 by HAUSP is an important pathway for p53 stabilization

Abstract: The p53 tumour suppressor is a short-lived protein that is maintained at low levels in normal cells by Mdm2-mediated ubiquitination and subsequent proteolysis. Stabilization of p53 is crucial for its tumour suppressor function. However, the precise mechanism by which ubiquitinated p53 levels are regulated in vivo is not completely understood. By mass spectrometry of affinity-purified p53-associated factors, we have identified herpesvirus-associated ubiquitin-specific protease (HAUSP) as a novel p53-interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
804
4
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 924 publications
(855 citation statements)
references
References 29 publications
37
804
4
5
Order By: Relevance
“…Deubiquitinating enzymes (DUBs) have been established as yet another critical modulator of p53 stability, the most notable example being HAUSP (herpesvirus-associated ubiquitin-specific protease), which has been shown to deubiquitinate p53, Mdm2 and Mdm4 in a concentration-dependent manner (Li et al, 2002;Meulmeester et al, 2005). More recently, USP2a (ubiquitin-specific protease 2a) has been identified as a novel DUB that selectively targets Mdm2, unlike HAUSP, and thereby offers another potential approach of therapeutic intervention to reactivate WT p53 (Stevenson et al, 2007).…”
Section: Targeting the P53 -Mdm2 Interactionmentioning
confidence: 99%
“…Deubiquitinating enzymes (DUBs) have been established as yet another critical modulator of p53 stability, the most notable example being HAUSP (herpesvirus-associated ubiquitin-specific protease), which has been shown to deubiquitinate p53, Mdm2 and Mdm4 in a concentration-dependent manner (Li et al, 2002;Meulmeester et al, 2005). More recently, USP2a (ubiquitin-specific protease 2a) has been identified as a novel DUB that selectively targets Mdm2, unlike HAUSP, and thereby offers another potential approach of therapeutic intervention to reactivate WT p53 (Stevenson et al, 2007).…”
Section: Targeting the P53 -Mdm2 Interactionmentioning
confidence: 99%
“…137,138 This significant accumulation of factors involved in p53 regulation raises the assumption that PMLNBs form supramolecular scaffolds that establish a peculiar molecular microenvironment enabling efficient post-translational modification of a fraction of p53. Similar to most PML-NB components, p53 is not a constitutive resident and its recruitment to PML-NBs is mediated by all PML isoforms, 16 but only interaction with PML IV regulates p53 activity.…”
Section: Regulation Of P53 Activity In Pml-nbsmentioning
confidence: 99%
“…52 Recently, the deubiquitinating enzyme HAUSP, which colocalises with PML-NBs, 137 was found to stabilise p53 and to activate its proapoptotic activity. 138 Whether HAUSP can exert its function in PML-NBs remains to be studied.…”
Section: Regulation Of P53 Activity In Pml-nbsmentioning
confidence: 99%
“…HAUSP can deubiquitinate p53, Mdm2 and MdmX and overexpression of HAUSP prevents p53 degradation. However, the balance of activity of endogenous HAUSP is such that its knockdown or knockout results in destabilization of Mdm2 and MdmX and stabilization of p53 (Li et al, 2002(Li et al, , 2004Cummins et al, 2004;Meulmeester et al, 2005). We have previously shown that USP2a can deubiquitinate Mdm2 without reversing Mdm2-mediated p53 ubiquitination (Stevenson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%